ANALISIS KADAR LOGAM TIMBAL (Pb) PADA RAMBUT KARYAWAN SPBU - Mayaserli, Dyna Putri; Renowati, Renowati; Biomed, M (Sainstek : Jurnal Sains dan Teknologi, 2017)
Development in the field of health is the achievement of an optimal public health degree. Among people who are often exposed to air pollution such as lead metal (Pb) is a gas station officer. One of the objectives of this research is to figure out the differences of lead level (Pb) in the hair of SPBU workers who base on Jl. Ir. Juanda based on length of service period by using experimental research to analyze Pb metal at gas station workers. The population and sample of research is hair of three gas station workers that contains metal of lead (Pb). The results of this study revealed that the longer employment period of workers, the higher the Pb level in their hair and the percentage recovery value for the wet destruction method using HNO3 and HCLO4 has an average recovery of 96.23% which is the precision test value of 4.01%. It is recommended that the validation test then use another method of dry destruction and examine the identity of age, place of birth date and lifestyle.